2014
DOI: 10.1136/oemed-2013-101896
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function and plasma BDNF levels among manganese-exposed smelters

Abstract: Mn exposure may be associated with decreased plasma BDNF levels and cognition impairment in this large cross-sectional study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 42 publications
(44 reference statements)
0
23
1
Order By: Relevance
“…Meanwhile, our previous studies showed that plasma BDNF levels are also associated with the extent of Mn exposure and cognitive impairments in Mn-exposed workers Zou et al, 2014). In the present study, the plasma BDNF levels were negatively correlated with the Mn treatment dose; by contrast, the plasma BDNF levels were positively correlated with the hippocampal BDNF levels.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Meanwhile, our previous studies showed that plasma BDNF levels are also associated with the extent of Mn exposure and cognitive impairments in Mn-exposed workers Zou et al, 2014). In the present study, the plasma BDNF levels were negatively correlated with the Mn treatment dose; by contrast, the plasma BDNF levels were positively correlated with the hippocampal BDNF levels.…”
Section: Discussioncontrasting
confidence: 51%
“…However, whether plasma BDNF can be a biomarker of Mn-induced cognitive deficits in the body remains unknown. Combined with our previous study Zou et al, 2014), plasma BDNF levels are associated with Mn exposure levels and cognitive impairment in Mn-exposed workers. Therefore, we assessed plasma BDNF levels to investigate whether plasma BDNF can be a reliable effect biomarker of Mn…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…On the other hand, high manganese levels can be neurotoxic. Excessive levels of manganese lead to cognitive impairments and extrapyramidal symptoms 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The Montreal Cognitive Assessment (MoCA) is a neurocognitive function test which rapidly screens for mild cognitive impairment with high sensitivity and specificity 20–22. We assessed the affect of Mn exposure on the nervous system using the MoCA as a cognitive screening tool 23. The Non-Motor Symptoms Scale (NMSS) and the Scales for Outcomes in Parkinson's Disease-Autonomic (SCOPA-AUT) are neurobehavioral function tests.…”
Section: Methodsmentioning
confidence: 99%